Does Social Security Crowd out Private Wealth? A Survey of the Literature - Wroński, Marcin (Journal of Economic Analysis, 2023)
In this paper, we review the research on the substitution between social security wealth and private wealth. Our review includes over 100 theoretical and empirical contributions. Nearly 70% of the literature identifies the statistically significant impact of social security wealth on different forms of private savings. A strong majority of authors, who obtain statistically significant results find the negative impact of social security on private savings. We discuss the main limitations of the literature.